Hsa_circ_0000745 promotes cervical cancer by increasing cell proliferation, migration, and invasion. Issue 2 (29th June 2019) - Jiao, Jun; Zhang, Teng; Jiao, Xinlin; Huang, Tingting; Zhao, Lu; Ma, Daoxin; Cui, Baoxia
Abstract: Circular RNAs (circRNAs) participate in gene regulation and malignant tumor progression, including uterine cervical cancer (CC). In this study, the expression profile of circRNAs in CC was detected using circRNA microarrays. Then, we selected hsa_circ_0000745 for further examination from the significantly dysregulated circRNAs. Proliferation assays, Transwell assays, quantitative reverse transcription polymerase chain reaction, western blot analysis and tumorigenesis tests in vivo were used to validate the role of hsa_circ_0000745 in CC. hsa_circ_0000745 was upregulated in CC, and its level positively correlated with the level of its linear messenger RNA isoform. Patients with poorly differentiated tumors or vascular/lymphatic invasion presented higher expression of hsa_circ_0000745. The role of hsa_circ_0000745 was illuminated by knocking down hsa_circ_0000745 in CC cells, and the results revealed that reducing hsa_circ_0000745 inhibited cell proliferation, migration, and invasion in CC by upregulating E‐cadherin (E‐cad) expression. In summary, as a tumor promoter in CC, hsa_circ_0000745 enhances the cell's ability to proliferate, migrate, and invade by reducing the expression of E‐cad. hsa_circ_0000745 is a candidate target for the treatment of CC in the clinic. Abstract : Hsa_circ_0000745 is upregulated and functions as a tumor promoter in cervical cancer. Hsa_circ_0000745 enhances the cell's ability to proliferate, migrate, and invade by reducing the expression of E‐cadherin in cervical cancer.